Kesetaraan Gender dalam Pembelajaran Sekolah Dasar Antara Pemahaman Guru dan Praktik Pembelajaran - Alethea Otsu Khoirunisa; Karsono Karsono; Matsuri Matsuri (Universitas Sebelas Maret, 2026)
This research is motivated by the persistence of gender stereotyping practices in elementary school learning, even though the Independent Curriculum has provided space for more inclusive and equal education. This study aims to describe elementary school teachers' perspectives on gender equality education and its implementation in learning. Methods: This study used a qualitative approach with ethnographic methods through observation, interviews, and document analysis. Results: The results show that teachers have a positive understanding of the concept of gender equality and recognize the importance of providing equal opportunities for male and female students. However, in learning practices, a hidden curriculum is still found that indirectly reinforces gender stereotypes through interactions, language use, and role divisions in the classroom. The implementation of gender equality also still depends on the awareness and interpretation of each teacher. Implications: This study shows that gender equality needs to be understood as a contextual and dynamic social practice, and emphasizes the importance of increasing teacher awareness, implementing inclusive learning strategies, and supporting school policies in creating a learning environment that is responsive to gender equality.